Autoubiquitination of the 26S Proteasome on Rpn13 Regulates Breakdown of Ubiquitin Conjugates. (8th May 2014) - Besche, Henrike C; Sha, Zhe; Kukushkin, Nikolay V; Peth, Andreas; Hock, Eva‐Maria; Kim, Woong; Gygi, Steven; Gutierrez, Juan A; Liao, Hua; Dick, Lawrence; Goldberg, Alfred L
Abstract Degradation rates of most proteins in eukaryotic cells are determined by their rates of ubiquitination. However, possible regulation of the proteasome's capacity to degrade ubiquitinated proteins has received little attention, although proteasome inhibitors are widely used in research and cancer treatment. We show here that mammalian 26S proteasomes have five associated ubiquitin ligases and that multiple proteasome subunits are ubiquitinated in cells, especially the ubiquitin receptor subunit, Rpn13. When proteolysis is even partially inhibited in cells or purified 26S proteasomes with various inhibitors, Rpn13 becomes extensively and selectively poly‐ubiquitinated by the proteasome‐associated ubiquitin ligase, Ube3c/Hul5. This modification also occurs in cells during heat‐shock or arsenite treatment, when poly‐ubiquitinated proteins accumulate. Rpn13 ubiquitination strongly decreases the proteasome's ability to bind and degrade ubiquitin‐conjugated proteins, but not its activity against peptide substrates. This autoinhibitory mechanism presumably evolved to prevent binding of ubiquitin conjugates to defective or stalled proteasomes, but this modification may also be useful as a biomarker indicating the presence of proteotoxic stress and reduced proteasomal capacity in cells or patients.